If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 3x = 6x + 26 Reorder the terms: 8 + 3x = 26 + 6x Solving 8 + 3x = 26 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 8 + 3x + -6x = 26 + 6x + -6x Combine like terms: 3x + -6x = -3x 8 + -3x = 26 + 6x + -6x Combine like terms: 6x + -6x = 0 8 + -3x = 26 + 0 8 + -3x = 26 Add '-8' to each side of the equation. 8 + -8 + -3x = 26 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 26 + -8 -3x = 26 + -8 Combine like terms: 26 + -8 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x | | 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 | | -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 | | -2x+12-2x=-5(x-2)+2 | | 3x+5x=850 | | 12+10=14y-3y | | -2x+10-3x=-5(x-2)+2 | | 8-6x-3=-21+4x-14 | | 7(x+2)=9x+2 | | 2(1x+8)=12 | | 6x^2-12=5x^2-4x | | X/12=34 | | -1x+12-3x=-5(x-2)+2 | | 18y^2-7y-2=0 | | 4x-x+9=(x+2)+p | | g(-1)forg(t)=(t^2-1)(t+4) | | 4n-2=4n-6 | | -2x+11-3x=-5(x-2)+2 | | 4+77x=44x+16 | | X-(-8)=15.6 | | 2x+6=-22-5x | | -2x+12-3x=-5(x-2)+2 | | 5(-3+6x)=-15 | | -1/3-g=-1/3 |